Incidental Finding of Intraperitoneal Tuberculosis in a Patient Presenting with a Large Ovarian Mass. (9th September 2018) - Green, Ayla; Elmasry, Samer; Ihalagama, Himali; Senaratne, Saman
Abstract : A 52-year-old postmenopausal female of Filipino heritage presented with a three-day history of increasing abdominal bloating, vomiting, and fever. A CT scan revealed a 22 cm ovarian mass and ascites. Her laboratory results were unremarkable except for CA-125 and CA-19.9 which were slightly elevated. Due to suspicion of ovarian neoplasm, she underwent a laparotomy where multiple inflammatory deposits were observed throughout the pelvis. Histology confirmed florid granulomatous inflammation with caseous necrosis, and peritoneal fluid culture was positive for tuberculosis. She was treated with standard antimycobacterial therapy and made an uneventful recovery.